2014
DOI: 10.1155/2014/491510
|View full text |Cite
|
Sign up to set email alerts
|

Fault Diagnosis of Beam-Like Structure Using Modified Fuzzy Technique

Abstract: This paper presents a novel hybrid fuzzy logic based artificial intelligence (AI) technique applicable to diagnosis of the crack parameters in a fixed-fixed beam by using the vibration signatures as input. The presence of damage in engineering structures leads to changes in vibration signatures like natural frequency and mode shapes. In the first part of this work, a structure with a failure crack has been analyzed using finite element method (FEM) and retrospective changes in the vibration signatures have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…They have also analyzed the beam numerically by using ANSYS. In Thatoi, Choudhury, Jena and Kumar (2014), the authors have used modified fuzzy technique to analyze the crack in a fixed-fixed beam. They have also validated the results numerically with ANSYS and also validated through experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…They have also analyzed the beam numerically by using ANSYS. In Thatoi, Choudhury, Jena and Kumar (2014), the authors have used modified fuzzy technique to analyze the crack in a fixed-fixed beam. They have also validated the results numerically with ANSYS and also validated through experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…The MFs are defined by the parameters based on the author's experience. Some of the researchers have used genetic algorithms to fuzzy logic together, but in this case the results from the genetic algorithm layer is trained again in the fuzzy logic layer for refinement (Dash and Parhi, 2014), some have used hybridized membership functions to be applied in the fuzzy inference system (Thatoi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…From the literature survey, it has been found that less work has been done hybridizing CSA and FLS and few of them are applied to the fault detection of cracked structures. Dash and Parhi (2014) and Thatoi et al. (2014) have proposed two different types of hybrid methods using FL for fault diagnosis of beam-like structure.…”
Section: Introductionmentioning
confidence: 99%